Oral helth behaviors, awareness, and knowledge among undergraduate students at the Faculty of Medicine in Bosnia and Herzegovina: A cross-sectional studya: Abstract - Cicmil, Ana; Cicmil, Smiljka; Lecic, Jelena; Govedarica, Olivera; Ivanovic, Tanja; Lucic, Marija; Joknic, Ilija; Krunic, Jelena (Medicinski časopis, 2026)
Introduction: The aim of this study was to assess oral hygiene habits, as well as awareness and knowledge among undergraduate students at a Faculty of Medicine in Bosnia and Herzegovina.Methods: This cross-sectional study was conducted at the Faculty of Medicine in Foča and included 333 students across three study programs: Medicine (M), Nursing (N), and Special Education and Rehabilitation (SER). The questionnaire was used to obtain demographic information, as well as data on oral hygiene habits and knowledge of oral health.Results: The largest proportion of students (56.2%) brush their teeth twice daily. A higher percentage of N and SER students brush their teeth longer than M students (p=0.004). Students most often replace their toothbrushes every 3 months or sooner (76.3%); 58.9% regularly visit a dentist; and 61% report no oral health problems. Only 14.4% of students believe that dental plaque dysbiosis is the cause of caries, while more than half of the students (53.5%) do not know the impact of dental plaque. Additionally, more than one-third of students (35.7%) are unaware of preventive measures for oral disease. A greater number of M and N students than SER students reported that oral health is related to cardiovascular disease (p=0.002), and more M students reported that it is related to cancer compared to SER students (p=0.032). Conclusion: The results of this study indicate limited knowledge of oral health among students across all three study programs, underscoring the need to improve oral health education for health sciences students.oralno-higijenske navike, oralno zdravlje, dentalni plak, mjere prevencije
Keywords: oral -hzgiene habits; oral health; dental plaque; prevention measures